Extramedullary hematopoiesis causing spinal cord compression in polycythemia vera: A case report and literature review - Axel Cailleteau; Komivi Agbetsivi; Valentine Guimas; Stéphane Supiot; Luc Ollivier (Clinical and Translational Radiation Oncology, 2023)
Extramedullary hematopoiesis (EMH) is a rare cause of spinal cord compression defined as finding hematopoietic elements outside the physiological location in the bone marrow. We report the case of a 70-year-old man with JAK 2 positive myeloproliferative syndrome type polycythemia vera (PV), initially treated with hydroxyurea. Two years after diagnosis, he presented progression with biological and clinical evolution associating hyperleukocytosis and hepatosplenomegaly with no evidence of acute myeloid leukemia. Treatment with hydroxyurea and ruxolitinib was introduced. Six months later, clinical symptoms suggesting spinal cord compression from the T2 region appeared. Medullary MRI revealed a multistage spinal cord injury from T2 to S1, while brain CT excluded any intracranial location. The biopsy diagnosed extramedullary hematopoiesis with no CD34 + blast cell, corresponding polycythemia vera. Given the lack of consensus and after a review of the literature, irradiation was planned to treat a volume from T1 to S2 with a dose of 18 Gy in 10 sessions of 1.8 Gy. At the end of the radiotherapy, the patient started to recover his motor and sensory functions. Six months later, he walked without assistance and had no significant acute toxicity. Using radiotherapy to treat spinal cord compression caused by EMH is justified with excellent early response and no major side effects. We present here this case and the systematic review of the literature on this matter.